PENINGKATKAN KESADARAN & KEPEDULIAN MASYARAKAT DALAM NEW NORMAL - Amanda Rosentia; Renny Christiarini; Nur Hidayati; Devin Tan; Elvin Whang; Rahel Nurhamidah; Hendri Gunawan; Cindy Ellysa; Dina Talantu; Nertivia Nertivia; Delfi Aurelia Kuasa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
At the beginning of 2020, almost all the countries are being renown in the case of Coronavirus (Covid-19), no exception to Indonesia. Indonesia is also currently facing Coronaviruses, as well as other countries. But the difference is that Indonesia is one of the countries with a lot of differences, ranging from the differentiation of tribes, cultures, races, religions, and many more. One of the ways Coronavirus prevention done by the Government of Indonesia is by issuing a new policy to prevent the spread of Coronavirus in the way of New Normal Life. Of course, there are many obstacles faced by Indonesians. One of the obstacles faced by Indonesian society is how can the people of Indonesia stay solid and together to fight the Covid-19 and run this New Normal policy. Therefore, in this program of Community Empowerment (Sepora 2020), we invite the people all to remain united with the effectiveness of differences by means of various information related to it, which aims to be united against COVID 19 and forget the difference as according to the motto of Indonesia, Bhinneka Tunggal Ika.